2020
DOI: 10.1007/s10815-020-01977-2
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing: a follow-up of 36,913 singleton pregnancies with noninvasive prenatal testing in central China

Abstract: Purpose To evaluate the noninvasive prenatal testing (NIPT) results of 36,913 cases in Jiangxi province of central China and explore its application value in prenatal screening and diagnosis. Methods This retrospective analysis included 36,913 singleton pregnant women who underwent NIPT because of moderate-/high-risk pregnancy or voluntary requirements between January 2017 and December 2019 in our hospital. Chromosomal abnormalities such as trisomies 21, 18, and 13 (T21, T18, T13) and sex chromosome aneuploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
4
5
1
8
Order By: Relevance
“…Recently, the detection range of NIPT has been expanding and has been extended to the screening of fetal chromosome microdeletion/microduplication syndrome (MMS), namely NIPT‐plus. Our results are consistent with previous domestic studies 30–32 . It is too early to judge the true sensitivity and false‐negative rate of SCAs in this study, because these clinical symptoms are not easily identified in neonatal examination and require long‐term prospective follow‐up 33 .…”
Section: Discussionsupporting
confidence: 88%
“…Recently, the detection range of NIPT has been expanding and has been extended to the screening of fetal chromosome microdeletion/microduplication syndrome (MMS), namely NIPT‐plus. Our results are consistent with previous domestic studies 30–32 . It is too early to judge the true sensitivity and false‐negative rate of SCAs in this study, because these clinical symptoms are not easily identified in neonatal examination and require long‐term prospective follow‐up 33 .…”
Section: Discussionsupporting
confidence: 88%
“…These data were mostly from China [ 8 – 10 , 13 20 ] and the United States [ 23 , 27 ], the Netherlands [ 24 ], Japan [ 22 ], Iran [ 25 ], and Italy [ 21 , 26 ]. The PPVs presented in this study were consistent with those in previous reports (Table 5 ) [ 9 , 15 17 , 19 , 20 ]. PPVs for T21 were higher than 84% in most reports, while only two reports had PPVs lower than 80% [ 10 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, limited methods can be used to screen SCAs, as the clinical features of most SCAs are not detectable during prenatal ultrasound examination because many develop after birth with the exception of structural anomalies more commonly seen in the Turner syndrome ( 1 , 5 7 ). With the discovery of circulating cell-free fetal DNA (cffDNA) in the blood samples of pregnant women and the advent of massively parallel genomic sequencing (MPS) technology, NIPT has been widely applied for the clinical screening for fetal chromosomal aberrations and has already expanded beyond the three common autosomal trisomies to include SCAs ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of reports have proven that NIPT is the most accurate screening test for trisomy 21, trisomy 18, and trisomy 13 with high sensitivity and specificity ( 9 22 ). However, limited studies have evaluated the accuracy of NIPT for screening SCAs ( 7 , 8 , 23 ).…”
Section: Introductionmentioning
confidence: 99%